Intermediasi Perbankan Syariah Terhadap Pertumbuhan Ekonomi Indonesia - Muhammad Putra Rizki; Fakhruddin Fakhruddin (Syiah Kuala University, 2015)
Sharia banking in Indonesia has been started for the last two decades. It was expected to have correlation and to contribute to higher economic growth in Indonesia. This research aimed to investigate the sharia banking intermediation in triggering economic growth in Indonesia. It used quarterly SBIS time-series data, total sharia financing, real sector growth and economic growth for the period of 2000:Q4 to 2012:Q4. Empirical findings indicated long run equilibrium between sharia banking and economic growth. Granger’s causality test implied bi-directional causality between real sector growth and economic growth and one direction causality from total sharia financing into real sector economy and economic growth. Estimation with Vector Error Correctin Model (VECM) tended to be inline with the hypothesis that sharia banking is able to serve as growth engine in Indonesia.